2008
DOI: 10.1080/14756360802205059
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modelling of phthalates – PPARs interactions

Abstract: Di(2-ethylhexyl) phthalate (DEHP) is the most widely plasticizer for polyvinyl chloride (PVC) that is used in plastic tubes, in medical and paramedical devices as well as in food storage packaging. The toxicological profile of DEHP has been evaluated in a number of experimental animal models and has been extensively documented. Its toxicity is in part linked to the activation of the peroxisome proliferator-activated receptor a (PPAR a ). As a response, an intensive research for a new, biologically inert plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…DEHP showed a slightly larger cluster of conformations in PPARa, corresponding to a third of the solutions, with its benzene at the very entrance of the pocket (Figure 2). A similar conformation was also found in the previous study, albeit with a lesser frequency 22 . Interestingly, DEHP also forms a number of hydrogen bonds, mostly with the skeletal NH of Ala 333 and the side chain of Thr 279.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…DEHP showed a slightly larger cluster of conformations in PPARa, corresponding to a third of the solutions, with its benzene at the very entrance of the pocket (Figure 2). A similar conformation was also found in the previous study, albeit with a lesser frequency 22 . Interestingly, DEHP also forms a number of hydrogen bonds, mostly with the skeletal NH of Ala 333 and the side chain of Thr 279.…”
Section: Resultssupporting
confidence: 70%
“…It did not induce developmental effects in rats following gavage treatment during gestation. This is probably due to its inability to fit into the binding sites of the PPARs receptors 22 . However, a single-generation study found no effects on reproductive function, but did report decreased spermatocyte and spermatid counts in males treated by gavage at high dose 18 .…”
Section: Resultsmentioning
confidence: 99%
“…A first study of their mechanism of action was devolved to PPAR [71], then a large virtual screening of 73 phthalate monoesters from the ACD database was performed on PPAR [72], leading to the discrimination between potential or already known agonists and putative inactive derivatives. A long standing interest in the effect of phthalate esters led us to investigate the binding mode of three derivatives, the diester di(2-ethylhexyl) phthalate (DEHP), its metabolite mono-ethylhexyl phthalate (MEHP) and a putative replacement as plasticizer, trioctyl trimellitate (TOTM) [73]. Apparently, TOTM is hardly able to fit into the pocket of PPAR due to its large size, while the smaller MEHP could occupy the pocket fairly easily and forms the hydrogen bonds network of classical agonists.…”
Section: Unrelated Ligandsmentioning
confidence: 99%
“…Moreover, PPARs plays an important role as a modulator of signal molecules that mediate alternations in gene expression of different enzymes involved in lipid homeostasis. Altered hepatic β oxidation pathways lead to medium and long chain fatty acids overload with subsequent increase of acyl coA activity that exceeds the free radicals elimination by catalase resulting in progressive DNA and parenchymal damage [24]. Marked periportal cellular infiltration was observable in DEHP treated subgroup IIA.…”
Section: Discussionmentioning
confidence: 97%